PERSEPSI MAHASISWI TERHADAP STANDAR KECANTIKAN YANG DI TAMPILKAN MEDIA SOSIAL (INSTAGRAM) - Dhea Cahyati Sihotang; Sere Natalia (Triwikrama: Jurnal Ilmu Sosial, 2025)
The purpose of this research is to identify if an individual is affected by the beauty standards being shown on social media, or have they made any changes on their physical appearance to fulfill the beauty standards, with the existence of Instagram beauty standards can make an individual feel insecure with their own appearance that makes them want to change with the current beauty standards, the theory that is being used in this research is Uses and Gratification where an individual is using the media platform to fulfill their needs and curiosity in the digital field, the method that is being used to collect data in this research is with an interview with the subject of Esa Unggul University students with Communication major that consist of 15 people, and based from their answers regarding the topic, majority of the students have agreed that the beauty standards in social media have affected them on their self-confidence and their will to change their physical appearance to fit into the beauty standards applied.